HUBUNGAN KADAR VITAMIN D DENGAN GLUKOSA DARAH PUASA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH - Fikri Alamsyah; Jelmila, Sri Nani; Nilas Warlem; Melya Susanti (Nusantara Hasana Journal, 2025)
Vitamin D plays an important role in various metabolic functions, including glucose regulation. Vitamin D deficiency has been increasing worldwide and is now a global health concern. Several studies have shown an association between low vitamin D levels and an increased risk of insulin resistance and impaired glucose metabolism. This study aims to determine the relationship between vitamin D levels and fasting blood glucose in medical students at the Faculty of Medicine, Baiturrahmah University, Padang. This study was an observational analytic study with a cross-sectional design. The research sample consisted of 52 medical students from the Faculty of Medicine, Baiturrahmah University. The mean vitamin D level was 23.35 ± 10.71 ng/ml. The mean fasting blood glucose level was 79.61 ± 1.17 mg/dl. The Spearman correlation analysis between serum vitamin D levels and fasting blood glucose showed an r-value of 0.04 and a p-value of 0.76. There was no significant relationship between vitamin D levels and fasting blood glucose.